Relationship of Vitamin D with Some Electrolytes in the Serum of People with Rheumatoid Arthritis in the City of Samarra - Adeeb Mahfooth Farag Al-Samaria1, Kader Abdullah Shanak Al-Esawi2, Esraa Ali Abdul Kareem Al-Samaria (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study was conducted on 50 samples of 30 patients with rheumatoid arthritis. The samples were divided into 15 females, 15 males and 20 control group (healthy) without any disease. The sample was divided into 8 females and 12 males. 80 years) and collected samples from Samarra General Hospital and outpatient clinics of the city. The blood was then collected from the healthy and sick people and separated by centrifugation. Biochemical variables were measured (vitamin D, glutathione , Mallon dialdehyde , uric acid). The results of the current study showed a significant decrease in the level of vitamin D in the serum of people with rheumatoid arthritis compared to healthy people, and the results showed a significant decrease in the level of glutathione in the serum of people with rheumatoid arthritis compared to healthy people, with no significant differences in Level of Mallon dialdehyde. We also note a significant increase in the level of uric acid in the serum of people with rheumatoid arthritis compared to healthy people.